Sage Extract as a Natural Source of Corrosion Inhibitor for Tinplate in 3.0% NaCl - Maja Dent; Regina Fuchs-Godec (Food Technology and Biotechnology, 2021)
Research background. Due to the growing interest and attention of the world towards environmental problems and protection of environment, the worldwide demand for biodegradable and effective corrosion inhibitors for tinplate has grown. Considering the diversity of the structures of polyphenols that are present in sage extract, it represents a promising potential source of low-cost and effective biodegradable green corrosion inhibitor for tinplate in 3.0% sodium chloride solution which is evaluated in this study. Experimental approach. Tafel polarisation and electrochemical impedance spectroscopy (EIS) at 25 °C have been used to evaluate the inhibitory activity of sage (Salvia officinalis L.) extract as a green inhibitor for the protection of tinplate from corrosion in 3.0% sodium chloride solution. Results and conclusions. We used electrochemical impedance spectroscopy to show that sage extract could serve as an effective inhibitor (94.1%) of the corrosion of tinplate in 3.0% NaCl at a mass concentration of 0.2 mg/L and temperature of 25 °C. The results obtained from potentiodynamic polarisation reveal that the sage extract acts as a mixed type inhibitor, with inhibition efficiency up to 82.5%, and the inhibition efficiencies calculated from EIS are in close agreement with these results. Attenuated total reflection-Fourier transform infrared spectroscopy (ATR–FTIR) results indicated that the inhibitory effect of the sage extract is due to the presence of a passivation layer on the tinplate surface, which consists of organic compounds such as polyphenols. These results confirm that the sage extract is more efficient in inhibiting the corrosion of tinplate at a concentration of 0.2 mg/L than at higher concentrations. Also, it shows good inhibition of tinplate in 3.0% sodium chloride solution. Novelty and scientific contribution. The exceptional corrosion inhibition potential of sage extract opens a door for its use and revalorization as a green corrosion inhibitor in the food industry.